Public access defibrillators: Gender-based inequities in access and application. (May 2020) - Grunau, Brian; Humphries, Karin; Stenstrom, Robert; Pennington, Sarah; Scheuermeyer, Frank; van Diepen, Sean; Awad, Emad; Al Assil, Rahaf; Kawano, Takahisa; Brooks, Steven; Gu, Bobby; Christenson, Jim
Abstract: Aim: While public access automated external defibrillator (AED) programs appear to improve outcomes in out-of-hospital cardiac arrest (OHCA) it is unclear if men and women benefit equally. We examined gender-based differences in OHCA location to determine what proportion were potentially eligible for public access AED application, and if patient gender was associated with AED utilization. Methods: We analyzed data from the Resuscitation Outcomes Consortium registry (2011–2015). We compared differences in OHCA locations by gender. We fit multivariate logistic regression models, restricted to public location OHCAs and public-location cases with bystander intervention, to calculate the association between gender and public access AED application. Results: Among 61 473 cases, 34% were female and 50% had bystander resuscitation. The incidence of public OHCA was 8.8% for women and 18% for men (risk difference 9.2%, 95% CI 8.7–9.7%). Women had significantly fewer OHCAs on roadways, in public buildings, places of recreation, and farms, but more in homes, non-acute healthcare facilities, and residential institutions. Female gender was associated with a lower odds of AED application in public OHCA (adjusted OR 0.76, 95% CI 0.64–0.90) and public-location cases with bystander interventions (adjusted OR 0.83, 95% CI 0.71–0.99). Conclusion: Women had fewer OHCA in public locations that may have public access AEDs. Even among public location OHCA with bystander interventions, women were less likely to have public access AED applied. Initiatives to optimize AED locations and to engage the public with gender-specific resuscitation training may improve outcomes in women with OHCA.